A tramitação da Lei Menino Bernardo e o apoderamento da demanda pelos campos político e midiático - Ávila, Francine Nunes (2015)
The present article aims to analyze the legislative production related to prohibition of children´s physical punishment in Brazil, according to Menino Bernardo Law 13.010/2014. The study intends to demonstrate the legislative´s appeal on exploitation of tragedy, victim and social outcry. Furthermore, it aims to show how the political field has taken advantage on this topic to promote itself with this law creation. A deductive approach was adopted, as well as monographic procedure and bibliographic research. With the conduct of Menino Bernardo Law, was possible to identify that politicians use all the demand and victimization, to include a new and repetitive law in the Brazilian legal system, which does not reflect on a real protection for children and teenagers. The first chapter presents the childhood and its identification and evolution using a historical and sociological approach, as well as legal legislationon childhood and adolescent protection, analysis of Law 7.672/2010 and Menino Bernardo Case. The second chapter shows the media’s role in the creation and production of this law, the tragedy’s construction and political interest. The third one, specially observe Bernardo Uglioni Boldrini case and its faults, questioning to whom it was addressed and which social groups it will be applied.